Effectiveness of sequences of One-Euro-Jobs: Is it better to do more One-Euro-Jobs or to wait? - Katharina Dengler (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2013)
Many studies have analysed the effectiveness of single active labour market programmes (ALMPs) for welfare recipients in different countries. As empirical evidence reveals that welfare recipients in Germany often participate in multiple programmes, I evaluate the sequential participation of unemployment benefit II (UB-II)-recipients in ALMPs in Germany. My study uses comprehensive, administrative data to control for dynamic selection that arises in the evaluation of sequences. Using a dynamic matching approach and an inflow sample of UB-II-recipients, I analyse the effects of sequences of One-Euro-Jobs and/or UB-II-receipt on labour market outcomes. I focus on two questions: Is participating in two consecutive One-Euro-Jobs compared with receiving UB II for two consecutive periods better for individuals' employment outcomes? Is it more effective to take part in a One-Euro-Job directly after entry into UB II or in a later period? For female participants in One-Euro-Jobs in the first period, especially in West Germany, I find that participating in two consecutive One- Euro-Jobs compared with receiving UB-II-receipt for two consecutive periods better facilitates integration into regular employment. It is also more effective for participants in One-Euro-Jobs in the first period to take part in a One-Euro-Job directly after entry into UB II rather than take part in a One-Euro-Job in a later period, especially for East German men (although not for West German women). However, I also find evidence of so-called programme careers and stepwise integration into regular employment through direct job creation schemes (without One-Euro-Jobs).
Keywords: C31; I38; J68; 330; sequences; dynamic matching; propensity score matching; activation; effect evaluation; One-Euro-Jobs